Finite Volume Element Method for a Nonlinear Parabolic Equation (Advances in Applied Mathematics and Mechanics, 2025)
In this article, we study a parabolic equation with both nonlinear time-derivative term and nonlinear diffusion term by the finite volume element method.The optimal error estimate in $H^1$-norm is proved for fully discrete scheme. The suboptimal error estimate in $L^2$-norm is proved both for semi-discrete scheme and fullydiscrete scheme. We prove the existence of solution for the fully discrete scheme. Numerical results show the effectiveness of our method.